El canto infantil para potenciar el lenguaje oral de las niñas y niños de 3 a 4 años de la unidad educativa Lauro Damerval Ayora de la ciudad de Loja. Período 2014-2015 - Jiménez Jiménez, Johana Fernanda (2016)
The present investigation dominated: The Child singing to enhance the oral language of children of 3-4 years old at Lauro Damerval Ayora Educative Unit of Loja City. Period 2014-2015. The Objective General was: To know the contribution of child singing as empowering source of oral language of children of 3-4 year old. The scientific, deductive, inductive, descriptive statistical and analytical synthetic methods were used. The techniques and instruments used for the preparation of this research work were: the survey for the teachers, the observation guide and activities that are aimed at children. The sample consisted of two teachers from the initial I parallel (A and B) and 32 students. The results obtained surveyed were: The 100% of teachers indicated that child singing is important for the development of oral language, in the guide observation: The 56% of the observed children is in process Oral Language Development. The post-guide showed that 55% of children dominated the Oral language. It is concluded that: 2% of children are not fluent in oral language as children do not express their ideas fluently. It is recommend teachers to explore the benefits of child singing and develop all the skills cognitive language motor in children to obtain a significant learning.